2016
DOI: 10.1080/17457289.2016.1243542
|View full text |Cite
|
Sign up to set email alerts
|

Preference votes without preference? Institutional effects on preference voting: an experiment

Abstract: A classical question of political science is to what extent electoral systems influence voting behaviour. Yet, many of these studies examine how different electoral systems affect the election results in terms of vote distribution across parties. Instead, we investigate how electoral rules affect intra party preference voting. Given the importance of the debate on the personalization of politics, insight into how electoral rules shape intra-party choice is a valuable contribution to the literature. In our stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 29 publications
0
14
0
Order By: Relevance
“…They suggest that the reason why voters vote for the head candidate is because she appears at the top of the list. Therefore, they do not have a genuine preference for this candidate(Nagtzaam, and van Erkel 2017). This literature usually comes from the Netherlands where elections are held under a flexible-list PR system, but where voters must vote for individual candidates (they cannot vote for the party-list).…”
mentioning
confidence: 99%
“…They suggest that the reason why voters vote for the head candidate is because she appears at the top of the list. Therefore, they do not have a genuine preference for this candidate(Nagtzaam, and van Erkel 2017). This literature usually comes from the Netherlands where elections are held under a flexible-list PR system, but where voters must vote for individual candidates (they cannot vote for the party-list).…”
mentioning
confidence: 99%
“…In the Netherlands, voters' options regarding preference votes are more constrained. Unlike Belgium, voters in the Netherlands do not have the option to cast a list vote, but are always forced to cast a vote for one single candidate on a party list (Nagtzaam & Van Erkel, 2017). Moreover, one cannot vote for multiple candidates.…”
Section: Preference Votes As Conceptmentioning
confidence: 99%
“…We argue that ballot structure is a relevant factor here. Whether voting for a candidate is optional or compulsory (in the sense that there is no formal way to simply express support for a party) is believed to be the most important difference between flexible list systems (Renwick and Pilet, 2016;Nagtzaam and van Erkel, 2017). Shugart (2005) even considers that flexible list systems in which the expression of preferences is made mandatory constitute a distinct sub-type, which he names latent list system.…”
Section: Why D O Voters Cast Preferential Ballot S In Flexible List Smentioning
confidence: 99%
“…In fact, their direct and longitudinal comparison of the aggregate percentage of preferential votes between countries is inconclusive: whereas Belgians tend to vote more preferentially than the Dutch, the Czechs and Swedes do so to a lesser extent (André et al, 2012;Renwick and Pilet, 2016). Nevertheless, an experiment carried out in the Netherlands and Belgium by Nagtzaam and van Erkel (2017), which analyzed the impact of different arrangements (not only compulsory vs. optional voting rules in flexible lists, but also the number of preferences voters are allowed to express) concluded that if expressing preferences is optional, fewer preferential votes will be cast.…”
Section: Why D O Voters Cast Preferential Ballot S In Flexible List Smentioning
confidence: 99%
See 1 more Smart Citation